2019
DOI: 10.1021/acs.nanolett.9b00508
|View full text |Cite
|
Sign up to set email alerts
|

124-Color Super-resolution Imaging by Engineering DNA-PAINT Blinking Kinetics

Abstract: Optical super-resolution techniques reach unprecedented spatial resolution down to a few nanometers. However, efficient multiplexing strategies for the simultaneous detection of hundreds of molecular species are still elusive. Here, we introduce an entirely new approach to multiplexed super-resolution microscopy by designing the blinking behavior of targets with engineered binding frequency and duration in DNA-PAINT. We assay this kinetic barcoding approach in silico and in vitro using DNA origami structures, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 25 publications
0
95
0
Order By: Relevance
“…This technique enables to image a virtually infinite number of targets in high resolution in the same sample. 20,21 Additionally, we observed that pre-mixing 1.Ab and 2.Nb can save time in staining thick biological samples imaged under light-sheet microscopy, ensuring also a better sample penetration and homogenous staining. Finally, we systematically compared the probe-induced clustering of the target protein either using directly-labelled monovalent probes, like affibodies and single Fab' fragments, and conventional 1.Abs detected by polyclonal and bivalent 2.Abs or by monovalent 2.Nbs.…”
Section: Introductionmentioning
confidence: 82%
“…This technique enables to image a virtually infinite number of targets in high resolution in the same sample. 20,21 Additionally, we observed that pre-mixing 1.Ab and 2.Nb can save time in staining thick biological samples imaged under light-sheet microscopy, ensuring also a better sample penetration and homogenous staining. Finally, we systematically compared the probe-induced clustering of the target protein either using directly-labelled monovalent probes, like affibodies and single Fab' fragments, and conventional 1.Abs detected by polyclonal and bivalent 2.Abs or by monovalent 2.Nbs.…”
Section: Introductionmentioning
confidence: 82%
“…25 These kinetic fingerprints will allow for additional freedom when designing Ago-PAINT. 29,31 Furthermore, optimization of the imager sequence and imaging conditions allowed for an order of magnitude faster imaging for conventional DNA-PAINT 32 . We expect that optimization of the Furthermore, as the imager strand is loaded and protected inside the protein, degradation of the imager strand is less likely to occur over time, unlike oligos that are rapidly digested.…”
Section: Resultsmentioning
confidence: 99%
“…DNA-PAINT has been widely used to image DNA origami type structures in vitro. [9][10][11][12][13][14][15][16][17][18][19][20] The enormous advantage of DNA-PAINT is that it is relatively straightforward to manipulate the specificity and affinity of the two interacting ssDNA strands. In more elaborate implementations, involving a ssDNA attached to a nanobody or aptamer for example, DNA-PAINT has been used to image proteins within fixed, permeabilized cells.…”
Section: Encoding Specificity Using Dna-paintmentioning
confidence: 99%